1994
DOI: 10.1182/blood.v83.12.3787.3787
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics associated with successful mobilizing and autografting of peripheral blood progenitor cells in malignant lymphoma

Abstract: For patients with advanced-stage or poor-prognosis malignant lymphoma, high-dose therapy with peripheral blood progenitor cell (PBPC) support may become a first-line treatment. The duration of severe cytopenia in this setting is inversely related to the number of PBPCs autografted. In a retrospective analysis, we therefore looked for factors influencing the yield of PBPCs in 61 patients (16 with high-grade and 29 with low-/intermediate-grade non-Hodgkin's lymphoma [NHL], and 16 with Hodgkin's disease) who rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
177
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(187 citation statements)
references
References 16 publications
8
177
0
1
Order By: Relevance
“…CD34 1 cell/ kg yield was reduced by 1.98 3 10 6 cells/kg per additional chemotherapy regimen given. A decrease in yield of 0.2 3 10 6 CD34 1 cells/kg per cycle of chemotherapy has been previously demonstrated by Haas et al [27]. No specific chemotherapy regimen was associated with higher mobilization failure rates.…”
Section: Discussionmentioning
confidence: 58%
“…CD34 1 cell/ kg yield was reduced by 1.98 3 10 6 cells/kg per additional chemotherapy regimen given. A decrease in yield of 0.2 3 10 6 CD34 1 cells/kg per cycle of chemotherapy has been previously demonstrated by Haas et al [27]. No specific chemotherapy regimen was associated with higher mobilization failure rates.…”
Section: Discussionmentioning
confidence: 58%
“…Secondly, the approximate number of CD34 + cells in the final products may be predicted from the HPC count in preapheresis PB. Moreover, the fact that the change in the number of HPCs closely resembled that of CD34 + cells in the PB during mobilization also suggested that HPCs in the PB may be a good indicator for the optimal timing of PBSC collection, as is CD34 + cell concentration [32,33,36] and SE/XE-determined HPC counts [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Thirdly, our data also suggested that the final CD34 + cell yield may be predicted from the HPC count in the mid-apheresis product.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Previously established risk factors for poor mobilization include multiple lines of chemotherapy, advanced age, thrombocytopenia, prior radiotherapy, and others. [10][11][12][13][14][15] In MM, multiple studies reported lenalidomide use to be another risk factor for poor mobilization. [16][17][18][19] Most studies use different definitions for poor mobilization in MM patients, mainly due to the practice of collecting upfront adequate numbers of stem cells for two transplants.…”
Section: Introductionmentioning
confidence: 99%